Young adults' reconciliation with their mournimg after parental loss between the ages of 11 and 18 - Coşkun, Duygu. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study aimed to examine a) the effects of adherence to mourning rituals, grief reactions, social environment, and coping strategies on adjustment to parental loss and b) to investigate the effects of gender, age of loss, sex of the lost parent and previous loss on young adults‟ adaptation to their lives. 25 female and 14 male native Turkish speaker undergraduate Boğaziçi University students participated in the study. The participants‟ attendance in grief rituals and environmental support after parental loss were measured by the Mourning Rituals Questionnaire (MRQ) and the Social Support Availability and Satisfaction Scale (SSASS), respectively. The Grief Reactions Scale (GRS) was used to evaluate grief responses, whereas the Coping with Parental Loss Scale (CPLS) investigated each participant‟s coping strategies during the mourning process. In order to assess each participant‟s adaptation to their new life, the Adjustment to Parental Loss Scale (APLS) was used. The results suggest that grief reactions have a negative effect on eventual adjustment to parental loss. According to the findings, it appears that losing a mother has a worse effect than losing a father; similarly losing a parent at a younger age has a worse effect in terms of adjustment to parental loss. However, no gender effects on young adults‟ adaptation after parental loss were found.|Keywords: mourning, grief, young adults, adolescent bereavement, parental loss.
Keywords: Parental grief.; Bereavement -- Psychological aspects.; Bereavement in youth.